AN ELASTIC ADHESION MODEL FOR TANGENTIAL TRACTION - Stefan GHIMISI (Fiabilitate şi Durabilitate)
The type of surface damage that occurs in fretting contact depends on the magnitude of the surface normal and tangential tractions. In existing fretting models the relative displacement is assumed to be accommodated mainly microslip in the contact surface. The present paper argues that adhesion forces and elastic deformation in the contact zone may contribute significantly to the relative displacement during fretting of metals .A simultaneously applied tangential force and normal into contact appears a adhesion force. A tangential force whose magnitude is less equal on greater than the force of limiting friction will not give rise on give rise to a sliding motion.It is determined the energy loss dissipated per fretting cycle.